PENGARUH KEPEMILIKAN MANAJERIAL, DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Nurzahara, Safarinda; Pratomo, Dudi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.11.TAHUN.2021, 2021)
Financial distress is a condition of a company's financial decline which if left unceasing can lead to bankruptcy or liquidation. To minimize the occurrence of financial distress, one way that can be used is by implementing good corporate governance. This research aims to analyze the effect of managerial ownership, independent boards of commissioners, and audit committees on financial distress disclosure in Textile and Garment sub-sector companies listed on IDX 2013-2017. The sample in this research amounted to 10 companies selected using the purposive sampling method, with a study period of 5 years, obtained 50 samples. The results showed that simultaneous managerial ownership, independent boards of commissioners, and audit committees had a significant effect on financial distress. Partially managerial ownership and the independent board of commissioners have a significant negative effect on financial distress, while the audit committee has a significant positive effect on financial distress.